USM EXTENDS COLLABORATION WITH UNIVERSITY OF LORRAINE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 15 June 2016 Since the first official contact between Universiti Sains Malaysia (USM) and University of Lorraine (UoL) in 1999 and the first MoU signed in 2002, USM has established a close relationship with UoL through many collaborative endeavours.